Designing a Product Storage System to Reduce the Number of Damaged and Expired Products at Alfa Omega Twin's Supermarket - Angela Reschyta Putri; Fransiska Hernina Puspitasari (Universitas Islam Raden Rahmat, Malang, 2026)
Good product storage systems in the warehouse affect product quality. The Alfa Omega Twin supermarket has a problem with damaged and expired products in total 46 units, resulting in a total loss of Rp559,500.00. After observation, the cause was found to be the haphazard placement of products and the absence of storage procedures. Thus, the research aims to reduce the number of damaged and expired products, also total losses. Due to the large number of products, ABC classification was used to categorize them. This classification will be used as the basis for designing a layout using class-based storage. Once the layout created, a storage standards using FIFO equipped with Standard Operating Procedures (SOP) was made. Based on the implementation results, the number of damaged and expired products decreased to nine and the total loss was Rp80,900.00. Employing both strategies through the storage arrangement and procedure, which is the distinction from other research can effectively address the problems. Practical tips on storage system that have been focused on those two strategies will assist a retail manager to keep the warehouse neat dan more organized.